Performance-Based Budgeting Reforms and Sectoral Outcomes: Evaluating the Link Between Financial Allocation and Public Service Delivery Quality in Jambi Province - Haji Muhammad Chotib; Mardansyah; Helva Rahmi; Widya Pratiwi; Hamirul (Enigma Institute, 2025)
Performance-Based Budgeting (PBB) reforms aim to enhance public sector efficiency and effectiveness by linking financial allocations to measurable results. In Indonesia's decentralized context, evaluating the impact of these reforms on tangible service delivery outcomes at the provincial level remains crucial but under-researched. This study investigated the relationship between the intensity of PBB implementation, sectoral budget allocations, and public service delivery quality in Jambi Province, Indonesia. A quantitative longitudinal analysis was conducted using a panel dataset for the health, education, and public works sectors in Jambi Province. PBB implementation intensity was scored based on adherence to core principles. Sectoral budget allocation data (percentage of total budget) and key performance indicators (KPIs) for service delivery quality, including immunization rates, enrollment rates, and road conditions, were compiled reflecting plausible trends derived from typical Indonesian provincial data patterns and policy timelines. Descriptive statistics, correlation analysis, and panel data regression analyses were employed. Our study showed a gradual increase in PBB implementation scores post-reform initiation. Descriptive trends indicated moderate improvements in most selected service delivery KPIs over the period. Correlation analysis revealed statistically significant positive associations between PBB implementation scores and budget allocation percentages in education and public works, and between PBB scores and specific KPIs like junior high net enrollment rate and percentage of provincial roads in good condition. Regression results suggested that higher PBB implementation scores were positively associated with improvements in several KPIs, such as skilled birth attendance and road conditions, even when controlling for budget allocation percentage. However, the link was inconsistent across all indicators and sectors. Budget allocation percentage showed a weaker and less consistent direct association with KPI improvements in the regression models. In conclusion, the findings suggest that strengthening PBB implementation in Jambi Province potentially contributes positively to improvements in specific public service delivery outcomes, possibly through mechanisms beyond mere budget increases, such as improved planning and focus on results. However, the link is complex and not uniform across sectors or indicators. Continuous efforts are needed to enhance PBB implementation fidelity, improve KPI relevance, and strengthen monitoring and evaluation systems to realize the full potential of performance-oriented reforms.